2019
DOI: 10.1080/09593969.2019.1664614
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing back from a sudden-onset extreme event: exploring retail enterprises’ resilience capacity

Abstract: The International Review of Retail, Distribution and Consumer Research Bouncing Back from a sudden-onset extreme event: exploring retail enterprises' resilience capacity.A feature of recent decades has been the sudden and unexpected occurrence of catastrophic events seriously affecting people and territories. From an economic viewpoint, this has led scholars to pay increasing attention to factors and determinants taking enterprises face-to-face with extreme and catastrophic events, through the resilience lens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…En este terreno de capacidades, se han abordado aquellas que fungen como antecedentes de la resiliencia, es el caso de las de venta, de orientación al mercado y de redes (Martinelli, De Canio y Tagliazucchi, 2019), la ambidestreza para atender demandas y adaptarse y la contingencia estratégica asociada a la continuidad de la organización (Iborra, Safon y Dolz, 2019). Además, al sugerirse la especialización del concepto de resiliencia, como ocurre con las cadenas de suministro, se ha llegado a incursionar en otras capacidades y recursos como la cultura de gestión del riesgo, la agilidad, la colaboración, la integración, la reconfiguración (para evitar futuras disrupciones) y el desempeño financiero (Al Naimi, Faisal, Sobh y Uddin, 2020; Chunsheng, Wong, Yang, Shang y Lirn, 2019).…”
Section: Análisis De Resultadosunclassified
See 1 more Smart Citation
“…En este terreno de capacidades, se han abordado aquellas que fungen como antecedentes de la resiliencia, es el caso de las de venta, de orientación al mercado y de redes (Martinelli, De Canio y Tagliazucchi, 2019), la ambidestreza para atender demandas y adaptarse y la contingencia estratégica asociada a la continuidad de la organización (Iborra, Safon y Dolz, 2019). Además, al sugerirse la especialización del concepto de resiliencia, como ocurre con las cadenas de suministro, se ha llegado a incursionar en otras capacidades y recursos como la cultura de gestión del riesgo, la agilidad, la colaboración, la integración, la reconfiguración (para evitar futuras disrupciones) y el desempeño financiero (Al Naimi, Faisal, Sobh y Uddin, 2020; Chunsheng, Wong, Yang, Shang y Lirn, 2019).…”
Section: Análisis De Resultadosunclassified
“…La resiliencia per se es considerada como una capacidad que evita los estragos de una situación adversa y propicia la regeneración (Linnenluecke, 2017;Martinelli et al, 2019); sin embargo, como lo señalan Ansell y Boin (2019), la falta de posesión de elementos cognitivos requeridos en los directivos de las organizaciones hace que no sea fácil de propiciarla en ellas, por lo que se cumple lo descrito por Barney (1991) sobre rareza, imitabilidad imperfecta y equivalentes estratégicos, a la vez de su utilidad en las organizaciones para ver oportunidades en la adversidad y atenuar sus amenazas.…”
Section: Precepto Teórico Con Mejor Aplicación Observada Para La Resi...unclassified
“…Pal et al (2014) have revealed that organizational resources such as materials, finance, leaders and employees are the main components of resilience. Focused on small retail enterprises, Martinelli et al (2019) have verified the positive influence of sales ability, market orientation, and network relationships on OR. Especially, previous studies mostly explored the impact of material resources, technical resources, human resources and economic resources on resilience from the perspective of organizational resources, but paid insufficient attention to the digital capability of service firms in the digital era.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 91%
“…Crises repeatedly force people to change habits and behaviors, both individually and collectively, including consumer behavior (Martinelli et al, 2019;Fuentes et al, 2022). Hall et al (2020) call for increased understanding of what, why and how consumption displacement occurs during crises.…”
Section: Crisis Consumptionmentioning
confidence: 99%